Factors of a social nature associated with prematurity risk in a city in São Paulo - da Cruz, Aline Adryane Morishigue Bássiga [UNESP]; dos Santos, Lucas Cardoso [UNESP]; de Oliveira Minharro, Michelle Cristine; Romanholi, Renata Maria Zanardo [UNESP]; Prearo, Alice Yamashita [UNESP]; Alencar, Rúbia Aguiar [UNESP] (Acta Paulista de Enfermagem, 2023)
Objective: To identify the associations of factors of a social nature with prematurity. Methos: This is a cross-sectional study with a correlational method, carried out from a database of a medium-sized municipality in the countryside of São Paulo, containing information on all newborns from January 2018 to July 2020, aimed at the identification of social and biological risks after birth. Results: The analysis included 4,480 newborns, of which 78.9% were classified as usual-risk babies and 21.1% as at-risk babies. Among the risk factors of a social nature for newborns analyzed in the present study, there was a higher prevalence of newborns whose head of household had no income, had mothers under 16 years of age, a dead sibling aged less than 5 years and mothers who did not undergo prenatal care, with the last two having association with prematurity. Conclusion: Factors of a social nature were associated with prematurity. This study made it possible to improve the newborn surveillance database, facilitating the elaboration and planning of health care.
Factores de naturaleza social asociados al riesgo de prematuridad en un municipio del estado de São Paulo
Fatores de natureza social associados ao risco de prematuridade em município paulista
Keywords: Infant, newborn; Infant, premature; Primary health care; Risk factors; Social vulnerability